2004
DOI: 10.1001/archinte.164.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of Digital Rectal Examination When Screening for Prostate Cancer

Abstract: Digital rectal examination is underutilized when screening for prostate cancer. This leads to nondetection of some prostate cancers. Although the DRE rate was poor among all health care providers, female providers and physician extenders outperformed male providers and physicians, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…A recent study found that DRE is underutilized when screening for prostate cancer, which can lead to nondetection of some prostate cancers [9].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that DRE is underutilized when screening for prostate cancer, which can lead to nondetection of some prostate cancers [9].…”
Section: Discussionmentioning
confidence: 99%
“…Women listen more and spend more time with patients . There are studies showing that women are better at making use of updated medical research findings, better at using diagnostic tools correctly and better at deciding when to operate on a patient . In addition, they work better in teams and manage complex problems more efficiently .…”
Section: Louise: Gender and Who Gets To Be A Heromentioning
confidence: 99%
“…However, there is good evidence to suggest that screening for prostate cancer increases its diagnosis at an early stage. The American Cancer Society and American Urology Association recommend screening with both digital rectal examination (DRE) and prostate-specific antigen (PSA) measurement [2]. DRE is the oldest and least invasive screening test for prostate cancer and serves as the initial diagnostic tool.…”
Section: Missed Digital Rectal Examination Missed the Primary Diagnosmentioning
confidence: 99%
“…This is the part of the gland that is easily accessible on DRE. Although DRE can detect prostate cancers, it has less sensitivity, specificity and positive predictive value than PSA as a screening tool for prostate cancers [1][2][3]. Despite the limitations of DRE, it should not be abandoned because 20% of prostate cancers may be associated with normal serum PSA and may be detected by DRE [1].…”
Section: Missed Digital Rectal Examination Missed the Primary Diagnosmentioning
confidence: 99%
See 1 more Smart Citation